Trematodes of the Genus Mesocoelium, Parasites of Anurans in the Ganzourgou Province, Burkina Faso - Soubeiga, Patricia; Boungou, Magloire; Sinaré, Yamba; Ayoro, Joelle H.; Kabre, Gustave B. (European Scientific Journal, ESJ, 2020)
The Trematodes of the genus Mesocoelium parasites of Anurans from Mogtedo, Zam, and Zorgho, in the area of Ganzourgou in Burkina Faso have been investigated between August, 2018 and January 2019. A total of 233 Anurans belonging to 5 families, 5 genera, and 9 species were examined. The species of Anurans examined were: Hoplobatrachus occipitalis, Amnirana galamensis, Ptychadena bibroni, Ptychadena pumilio, Sclerophrys pentoni, Sclerophrys maculata, Sclerophrys regularis, Sclerophrys xeros, and Xenopus fischbergi. The Anurans were collected by hand using the Visual Acoustic Encounter Survey (VAES) method. Amphibians were euthanized and dissected to examine the digestive tract and their appendices for Trematodes of the genus Mesocoelium. Atotal of9 species of the genus Mesocoelium were recovered, with an overall prevalence of 11.16%. The Trematodes that have been recovered were: Mesocoelium monas, Mesocoelium brieni, Mesocoelium sociale, Mesocoelium microon, Mesocoelium incognitum, Mesocoelium danforthi, Mesocoelium americanum, Mesocoelium monody, and Mesocoelium megaloon. The means intensity of infestation was generally low except for Mesocoelium incognitum (100.5 parasites / infested host). That infestation was influenced by the selectivity of the host by the Trematodes. It appears that in the 9 species of Anurans examined, only 3 species were infested by parasitic Trematodes (Hoplobatrachus occipitalis, Sclerophrys maculata and Sclerophrys regularis). The preferred organ of the genus Mesocoelium infestations in the host was the small intestine. Histopathologic studies in infested organs will be carried out to show the impacts of the Trematodes of the genus Mesocoelium in their hosts.